Peran Badan Penanggulangan Bencana Daerah Dalam Mengatasi Kekeringan Di Kabupaten Wonogiri - Krismona Dewi Arini; Asianto Nugroho (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
The purpose of this study was to determine the implementation of disaster management in Wonogiri Regency, as well as the technical and non-technical obstacles it faces. This research is a normative study with a statutory approach. The results showed that, the urgency of implementing drought disaster management in Wonogiri Regency based on the Regional Regulation of Wonogiri Regency Article 37 (2) Number 7 of 2016 through a juridical study is in accordance with vertical synchronization and harmonization of applicable laws and regulations. The Regional Disaster Management Agency of Wonogiri Regency as a disaster management task force through the Regional Budget Fund, in accordance with its authority has implemented disaster management during pre-disaster, emergency response, and post-drought disaster in 2017, 2018, 2019, and until the end. in August 2020 with the assistance of donors in the Wonogiri Regency area and from outside Wonogiri Regency.